POLITENESS STRATEGIES APPLIED IN SYNCHRONOUS ONLINE LEARNING - Afifah, Fadhilah Nur; Arianti, Theresia (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Politeness strategies are often found in everyday interaction. Research related to politeness strategies needs to be updated considering that language continues to evolve. Therefore, this study aims to analyze the types of politeness strategies and sociological factors that influence the teacher in choosing certain politeness strategies during synchronous online learning at SMK Negeri 42 Jakarta. In conducting the research, the researcher analyzed the data by referring to the politeness strategy theory proposed by Brown and Levinson (1987). The result of this study shows that there are four types of politeness strategies applied by the teacher, including bald on-record, positive politeness, negative politeness, and off record strategy with positive politeness as the type of politeness strategy that is most often used by the teacher in her teaching. Social distance and relative power were also investigated as sociological factors that influence the teacher in choosing certain type of politeness strategy. The analysis of the implementation of the politeness strategy in two English teaching and learning videos have been further explained in the results and discussion section.